Cancer Cells Exploit Notch Signaling to Redefine a Supportive Cytokine Milieu - Colombo, Michela; Mirandola, Leonardo; Chiriva-Internati, Maurizio; Basile, Andrea; Locati, Massimo; Lesma, Elena; Chiaramonte, Raffaella; Platonova, Natalia (Frontiers in Immunology, 2018)
Notch signaling pathway is well known for its key role in the communication between adjacent cells during development where it controls several processes involved in physiologic tissue differentiation. Notch-mediated communication may involve neighboring cells through mechanism of lateral induction activated by the interaction of Notch receptors with ligands on adjacent cells or may occur in a paracrine or endocrine fashion through the release of soluble molecules that can mediate the communication between cells at distant sites. Dysregulation of Notch pathway causes different disorders including cancer. Here Notch hyperactivation may be due to mutations of Notch related genes, upstream dysregulated pathways or microenvironmental cues. Cancer cells may exploit this aberrant signaling to “educate” the surrounding cells of the microenvironment toward a pro-tumoral behavior. This may occur by inducing tumor cells to secrete key cytokines or may involve the microenvironment through the activation of Notch signaling in the surrounding stromal cells mediated by a direct cell-cell contact and resulting in the increased secretion of several pro-tumorigenic cytokines and chemokines. Here we provide an overview on the outcomes of the Notch-mediated pathological communication in different tumor settings, the molecular mediators involved along with the engaged cellular players of the microenvironment. We describe how Notch dysregulation in cancer may alter the cytokine network and its outcomes on tumor progression - i.e. proliferation and senescence, angiogenesis, metastasis and pharmacological resistance – and subvert the anti-cancer immune system response and the inflammatory status.